Analysis of Blade Profile Effects on Performance of Wells Turbine as Wave Energy Converter using CFD Method - Muhammad Anis Mustaghfirin; Niki Veranda Agil Permadi; Jeheskiel Surbakti (International Journal of Marine Engineering Innovation and Research, 2024)
An oscillating water column (OWC) is a type of power generation device that converts ocean wave energy into electrical energy. The motion of ocean waves forces air through the OWC column and drives a rotor connected to a generator to produce electricity. The Wells turbine is a typical kind of rotor for OWC system. The performance of the Wells turbine can be influence by various factor, such as its geometry. Over the time, various research have been conducted to enhance the Wells turbine design. This study aims to analyze the impact of blade profiles on an 8-bladed Wells turbine’s performance using the Computational Fluid Dynamics (CFD) method. A full-domain with multiple reference frame (MRF) approach is applied to represent the rotating flow of the turbine. The flow is solved using Reynold Average Navier-Stokes (RANS) solver accompanied by shear stress transport turbulunce model to capture the boundary layer near the wall. In this study, some blade profiles including NACA 0012, NACA 0015, and NACA 0018, with chord lengths of 100 mm, 125 mm, and 150 mm, are examined. The results of this study reveal that the NACA 0018 blade profile with a 150 mm chord length improves the torque coefficient by 36.28% and the power coefficient by 1.04% compared to other configurations.